Additional Constraints to Ensure Three Vanishing Moments for Orthonormal Wavelet Filter Banks and Transient Detection - Uzinski, J. C.; Paiva, H. M.; Villareal, F.; Duarte, M. A. Q.; GalvÃo, R. K. H. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2015)
This article presents an improvement to the formulation of Sherlock and Monro for the wavelet parameterization for the obtainment of the restrictions which ensure three vanishing moments. In order to test the formulation presented, a transient signal detection is presented.

Este artigo apresenta uma melhoria para a formulação de Sherlock e Monro para a parametrização wavelet para a obtenção das restrições que garantem três momentos nulos. A fim de testar a formulação apresentada, um exemplo de detecção de transitórios em sinais é apresentada.
Keywords: vanishing moments; additional constraints; transient detection; Momentos nulos; restrições adicionais; detecção de transitórios